Pengaruh Psychological Empowerment terhadap Work Engagement pada Dosen - Regina Oktaviania Aurel; Hendro Prakoso; Vici Sofianna Putera (UNISBA Press, 2023)
Abstract The aim of this study is to determine the influence of psychological empowerment on lecturer’s work engagement. The amount of sample is 95 lecturers from Universitas Islam Bandung, Universitas Pendidikan Indonesia, and Universitas Pasundan. Measurement of psychological empowerment using psychological empowerment scale from Spreitzer and utrechts work engagement scale-17 from Schaufeli & Bakker for work engagement, adapted by Sutisna, et al (2020). Multiple regression is used for analytical data. The result of this study indicates that psychological empowerment has an effect on work engagement by 49.3% with meaning and competence giving a large effect on work engagement. Abstrak. Penelitian ini bertujuan untuk mengetahui seberapa besar pengaruh psychological empowerment terhadap work engagement dosen. Jumlah sampel dalam penelitian ini adalah 95 dosen yang berasal dari Universitas Islam Bandung, Universitas Pendidikan Indonesia dan Universitas Pasundan. Alat ukur yang digunakan adalah alat ukur psychological empowerment scale dari Spreitzer dan alat ukur utrechts work engagement scale-17 (UWES-17) dari Schaufeli & Bakker yang diadaptasi oleh Sutisna, et al (2020). Analisis data yang digunakan adalah multiple regression. Berdasarkan hasil regresi ditemukan bahwa psychological empowerment memiliki pengaruh yang besar terhadap work engagement sebesar 49,3% dengan dimensi meaning dan competence yang memberikan pengaruh paling besar terhadap work engagement.